2022
DOI: 10.1101/2022.01.26.477917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preclinical stage abundance and nuclear antigen reactivity of fecal Immunoglobulin A (IgA) varies among males and females of lupus-prone mouse models

Abstract: Systemic lupus erythematosus (SLE) is characterized by the production of pathogenic autoantibodies with nuclear antigen (nAg) specificity. Using (SWRxNZB)F1 (SNF1) mice, we showed higher levels of IgA production in the intestine and the nAg reactivity of fecal IgA under lupus susceptibility. Here, we determined if the fecal IgA abundance and nAg reactivity are higher in, different among, various lupus-prone preclinical models (MRL/lpr, NZBxNZW-F1, SNF1, NZM2410 and NZM2328). We also determined if the fecal IgA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In this regard, it would be informative to determine if fecal IgA and subclass features and Zonulin alter during active disease flares in SLE patients. Furthermore, although additional studies using longitudinal samples from subjects who are susceptible to SLE are needed, our current observations in the context of our preclinical studies [6,7] suggest the potential biomarker value of fecal IgA features alone or along with Zonulin levels, in predicting the ongoing autoimmune process, if any, in at-risk subjects.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this regard, it would be informative to determine if fecal IgA and subclass features and Zonulin alter during active disease flares in SLE patients. Furthermore, although additional studies using longitudinal samples from subjects who are susceptible to SLE are needed, our current observations in the context of our preclinical studies [6,7] suggest the potential biomarker value of fecal IgA features alone or along with Zonulin levels, in predicting the ongoing autoimmune process, if any, in at-risk subjects.…”
Section: Discussionmentioning
confidence: 78%
“…High levels of circulating autoantibodies and immune-complexes (IC), and IC deposition in the kidney causing glomerulonephritis are the hallmarks of SLE [1,2]. Our preclinical studies using lupus-prone mice have shown: 1) that minor dietary deviations can alter the composition of gut microbiota and the lupus-like disease progression [3], 2) a potential contribution of pro-inflammatory immune response, including higher frequencies of plasma cells, initiated in the gut mucosa to the disease process and gender bias [4,5], 3) higher frequencies of IgA-autoantibody producing cells in the gut mucosa, and 4) higher abundance and nAg reactivity of fecal IgA at pre-seropositive and -clinical stages [6,7]. Importantly, higher gut permeability and microbial translocation have been implicated in the initiation and/or progression of autoimmunity in at risk subjects [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of circulating autoantibodies and immune-complexes (IC), and IC deposition in the kidney causing glomerulonephritis are the hallmarks of SLE [1, 2]. Our preclinical studies using lupus-prone mice have shown: 1) that minor dietary deviations can alter the composition of gut microbiota and the lupus-like disease progression [3], 2) a potential contribution of pro-inflammatory immune response, including higher frequencies of plasma cells, initiated in the gut mucosa to the disease process and gender bias [4, 5], 3) higher frequencies of IgA-autoantibody producing cells in the gut mucosa, and 4) higher abundance and nAg reactivity of fecal IgA at pre-seropositive and -clinical stages [6, 7]. Importantly, higher gut permeability and microbial translocation have been implicated in the initiation and/or progression of autoimmunity in at risk subjects [8, 9].…”
Section: Introductionmentioning
confidence: 99%